2021
DOI: 10.1186/s12889-021-12213-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to facility HIV self-testing in outpatient settings in Malawi: a qualitative study

Abstract: Background Facility HIV self-testing (HIVST) within outpatient departments can increase HIV testing coverage by facilitating HIVST use in outpatient waiting spaces while clients wait for routine care. Facility HIVST allows for the majority of outpatients to test with minimal health care worker time requirements. However, barriers and facilitators to outpatients’ use of facility HIVST are still unknown. Methods As part of a cluster randomized trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Provision of private spaces as part of HIVST programs for viewing results is crucial to encourage shy adult women test for HIV. 27 Our study observed higher risk of opting out among urban populations as compared with rural residents for both men and women. This is consistent with other HIV testing studies that report low uptake of testing among urban populations across the region.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Provision of private spaces as part of HIVST programs for viewing results is crucial to encourage shy adult women test for HIV. 27 Our study observed higher risk of opting out among urban populations as compared with rural residents for both men and women. This is consistent with other HIV testing studies that report low uptake of testing among urban populations across the region.…”
Section: Discussionmentioning
confidence: 43%
“…Provision of private spaces as part of HIVST programs for viewing results is crucial to encourage shy adult women test for HIV. 27…”
Section: Discussionmentioning
confidence: 99%
“…The searches yielded 2,203 citations, of which, 11 studies were deemed eligible, including 4 randomized controlled trials [4,[13][14][15], 2 prospective single-arm cohort studies [16,17], 2 qualitative studies employing individually-based in-depth interviews (IDI) [18,19], 2 costing studies [20,21] and 1 costeffective analysis [22] (Figure 1). Malawi, including a costing study [20], a modelled cost-effectiveness study [22], and a qualitative study [18], targeting adolescent & adult outpatients in high burden health facilities. The remaining RCTs [13][14][15] were individual RCTs, targeting truck drivers and female sex workers at roadside wellness clinics in Kenya.…”
Section: Resultsmentioning
confidence: 99%
“…HIVST is consistently shown to increase testing rates in comparison with standard PITC models, even in randomized controlled trials where providers receive additional support for implementing PITC [ 11 , 12 , 14 , 21 ]. There is consensus that HIVST is associated with a higher absolute number of patients on treatment for HIV, although linkage rates differ based on the HIVST implementation [ 11 , 14 , 21 ] and antiretroviral treament (ART) initiation has been lower among those diagnosed through self‐testing in comparison to PITC [ 14 , 22 ]. Hybrid facility‐based PITC + HIVST strategies may allow health facilities to maximize the benefits of both modalities, increasing coverage and reducing personnel costs without sacrificing quality of and linkage to care.…”
Section: Discussionmentioning
confidence: 99%